NGF, BDNF, and NO in Myopic Subjects: Relationships Between Aqueous Levels and Lens Epithelial Cells’ Activation - De Piano, Maria; Cacciamani, Andrea; Scarinci, Fabio; Squitti, Rosanna; Cosimi, Pamela; Bruno, Marisa; Ripandelli, Guido; Palanza, Paola; Micera, Alessandra (International journal of molecular sciences, 2025)
Several soluble mediators are activated during myogenesis and progression, and severe neurodegeneration, with related biomarkers, characterizes high myopia-related retinal atrophy. Targets of oxidative stress, epigenetics and neurogenic inflammation have been reported in the prospecting of some bioindicators to mirror retinal insults occurring in high myopia. The aim of the present study was to assess the expression of a few selected biomarkers belonging to the neurotrophin (NGF and BDNF), oxidative (NO, KEAP1/NRF2), and epigenetic (DNMT3 and HD1) pathways. Sixty-five (65; 76.25 ± 9.40 years) specimens—aqueous, anterior capsule (AC), and lens epithelial cells (LEC)—were collected at the time of cataract surgery and used for ELISA (aqueous) and transcripts analysis (AC/LEC). Biosamples were grouped as emmetrope (23; 81.00 ± 6.70 years); myopia (24; 75.96 ± 7.30); and high (pathological) myopia (18; 70.56 ± 11.68 years), depending on axial length (AL) and refractive error (RE). Comparisons and correlations were carried out between myopic and high-myopic subgroups. NGF and BDNF were lowered in myopic samples; NGF and BDNF transcripts were differentially expressed in LEC, and their expression correlated positively with NGF and negatively with BDNF, with the expression of the αSMA phenotype. NGF and BDNF correlated negatively with NO and nitrites. Oxidative stress (iNOS/NOX1/NOX4 and KEAP1/NRF2) and epigenetic (DNMTα3/HD1) transcripts were upregulated in myopic LEC, compared with emmetropic ones. Herein, we prospect the contribution of NGF and BDNF in both neuroinflammation and neuroprotection occurring in this chronic disease.